Experimental Investigation of Seawater for the Absorption of Carbon Dioxide from Ship Chimneys - İrem Koçyiğit Çapoğlu; Duygu Uysal; Özkan Murat Doğan; Bekir Zühtü Uysal (Journal of Advanced Research in Natural and Applied Sciences)
Carbon dioxide (CO2) is the most important greenhouse gas that causes global warming. It is crucial to remove CO2 from the atmosphere to combat climate change. It is believed that seawater could be a potential source for capturing CO2, especially from ship chimneys and potentially high-concentration CO2 emissions in coastal regions. In this study, the CO2 absorption performance of sodium chloride (NaCl) solution as seawater, was investigated. The first phase of experiments was performed in a stirred cell at 91 kPa and 20°C. The total CO2 absorption capacity (molCO2L-1 solution) and dissolution rate (mols-1) of the solutions were determined by the pressure drop values occurring inside the cell. The experiments were conducted by preparing NaCl solutions at different concentrations (0-3.5 wt%). Additionally, 0.4% by volume calcium oxide (CaO) solution was added to NaCl solutions at different concentrations and its contribution to CO2 absorption was examined. It was observed that there was a decrease in CO2 absorption performance with the increase in salinity. However, it was determined that the addition of CaO to the NaCl solution had a positive effect on CO2 absorption performance and increased the total CO2 absorption capacity by 66%. The second phase of experiments was carried out in a falling film column. In these experiments, the liquid side individual physical mass transfer coefficients (kL0) were determined by the oxygen (O2) desorption method for pure water and 3.5 wt% NaCl solution. Also, nonlinear regression analyses were performed, and correlations were developed for mass transfer coefficients.